Osteotomies—When, Why, and How? - Locketz, Garrett D.; Lozada, Kirkland N.; Becker, Daniel G. (Facial Plastic Surgery, 2020)
An ideal nasal osteotomy should deliver precise, predictable, and reproducible cosmetic and functional results while minimizing soft-tissue trauma and postoperative complications. In addition to closing an open roof deformity after hump reduction, other common indications for osteotomies include the crooked nose and a wide bony vault. The literature has reported numerous and diverse osteotomy techniques as well as differences in timing of osteotomies. Each has its own merits and indications, and its proponents. In this article, we review the anatomy and nomenclature relating to osteotomies. We review the locations and paths of the osteotomies—lateral, intermediate, medial, and superior/transverse. We consider the percutaneous and endonasal approaches, as well as timing of osteotomies and other considerations. We also discuss technical considerations in the selection of instrumentation for osteotomies.
Keywords: osteotomies; open roof; endonasal; percutaneous